The influence tax transparency, trust, service quality on SME taxpayers' willingness to pay taxes in Bengkulu - Tri Lestari, Nur Hikmah; Fadli, Fadli (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The purpose of the research is to investigate and explain taxpayers' behavior, specifically their willingness to fulfill tax obligations, through the application of The Theory of Planned Behavior (TPB). Employing a quantitative-explanatory approach, this study specifically targets taxpayers involved in the SMEs industry. The sample size is determined using purposive sampling techniques, calculated through the Slovin formula, considering a total population of 3,883 SMEs in Bengkulu. The objective is to collect responses from 100 business actors in the SMEs industry, with selection criteria including individuals engaged in Micro, Small, and Medium Enterprises (MSMEs) in trade, industry, and services within Bengkulu, having a minimum business tenure of one year. Tax transparency has a positive and significant impact on the willingness to pay taxes. Trust has a positive and significant effect on the willingness to pay taxes. Service quality has a positive and significant impact on the willingness to pay taxes in Bengkulu City.